ASSESSMENT OF KNOWLEDGE, ATTITUDE AND PRACTICE TOWARDS CONSANGUINEOUS MARRIAGES AMONG A COHORT OF MULTIETHNIC HEALTH CARE PROVIDERS IN SAUDI ARABIA. Issue 1 (29th December 2016) - Alnaqeb, Dhekra; Hamamy, Hanan; Youssef, Amira M.; Al-Rubeaan, Khalid
Summary: This study aimed to assess knowledge, attitude and practice related to consanguinity among multiethnic health care providers in the Kingdom of Saudi Arabia. Using a cross-sectional study design, a validated, self-administered close-ended questionnaire was randomly distributed to health care providers in different health institutions in the country between 1st August 2012 and 31st July 2013. A total of 1235 health care providers completed the study questionnaire. Of the 892 married participants (72.23% of total), 11.43% were married to a first cousin, and were predominantly Arabs, younger than 40 years and male. Only 17.80% of the patients seen by the health care providers requested consanguinity related counselling. A knowledge barrier was expressed by 27.49% of the participants, and 85.67% indicated their willingness to have more training in basic genetic counselling. A language barrier was expressed as a limiting factor to counselling for consanguinity among non-Arabs. The health care providers had a major dearth of knowledge that was reflected in their attitude and practice towards consanguinity counselling. This finding indicates the need for more undergraduate and postgraduate medical and nursing education and training in the counselling of consanguineous couples. It is recommended that consanguinity counselling is included in the current premarital screening and counselling programmes in the Kingdom.